Identification of CD56dim subpopulation marked with high expression of GZMB/PRF1/PI‐9 in CD56+ interferon‐α‐induced dendritic cells. (29th March 2021) - Watanabe, Asuka; Togi, Misa; Koya, Terutsugu; Taniguchi, Makoto; Sakamoto, Takuya; Iwabuchi, Kuniyoshi; Kato, Tomohisa; Shimodaira, Shigetaka
Abstract: As the sentinels of innate and adaptive immune system, dendritic cells (DCs) have been considered to hold a great promise for medical application. Among the diverse types of DCs, monocyte‐derived DCs (mo‐DCs) generated in vitro have been most commonly employed. We have been improving the culture protocol and devised a protocol to produce mature interferon‐α‐induced DCs (IFN‐DCs), hereinafter called (mat)IFN‐DCs. While exploring the relationship between the expression of CD56 and the cytotoxic activity of (mat)IFN‐DCs, we unexpectedly found that sorting of (mat)IFN‐DCs with CD56 antibody‐coated microbeads (MB) resulted in fractionating cells with tumoricidal activity into the flow‐through (FT) but not MB‐bound fraction. We uncovered that the FT fraction contains cells expressing low but substantial level of CD56. Moreover, those cells express granzyme B (GrB), perforin (PFN), and serpin B9 at high levels. By employing a specific inhibitor of PFN, we confirmed that direct tumoricidal activity relies on the GrB/PFN pathway. We designated subpopulation in FT fraction as CD56 dim and that in CD56 positively sorted fraction as CD56 bright, respectively. This is the first time, to our knowledge, to identify subpopulations of CD56‐positive IFN‐DCs with distinct tumoricidal activity which is ascribed to high expression of the components of GrB/PFN pathway. Abstract : a; Scheme of strategy for sorting CD56 dim and CD56 bright subpopulation. b; Expression of CD56, GZMB, PRF1 and PI‐9 mRNAs in the cells of CD56 dim and CD56 bright subpopulation.